2020
DOI: 10.1017/langcog.2020.21
|View full text |Cite
|
Sign up to set email alerts
|

The role of non-categorical relations in establishing focus alternative sets

Abstract: Categorisation is arguably the most important organising principle in semantic memory. However, elements that are not in a categorical relation can be dynamically grouped together when the context provides a common theme for these elements. In the field of sentence (and discourse) comprehension, alternatives to a focused element can be thought of as a set of elements determined by a theme given in the utterance context. According to Alternative Semantics (Rooth, 1985, 1992), the main function of linguistic foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Thus, Jördens et al (2020) concluded that the set of alternatives that focus generates is contextually determined. The findings of Gotzner (2017) and Jördens et al (2020) support the permissive view of the generation of focus alternatives.…”
Section: Psycholinguistic Results On the Functional Aspects Of Focusmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, Jördens et al (2020) concluded that the set of alternatives that focus generates is contextually determined. The findings of Gotzner (2017) and Jördens et al (2020) support the permissive view of the generation of focus alternatives.…”
Section: Psycholinguistic Results On the Functional Aspects Of Focusmentioning
confidence: 99%
“…The variables of interest were response latencies (which we will refer to as RT for reasons of convenience) and accuracy (i.e., rates of correct acceptance and rejection). In line with the probe recognition literature (see e.g., Sturt et al, 2004 ; Sanford et al, 2006 ; Jördens et al, 2020 ), these variables are taken as correlates of activation level. Also, RTs and correct rejection rates are a measure of relatedness in the Different probe conditions, since items which bear no semantic (or any other) relation to the critical item, i.e., those that are completely unrelated, are expected to be rejected highly accurately and fast compared to those which are in closer relation to the critical item.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we saw, researchers often provide possible co-hyponyms in order to probe whether alternatives are active. There is nothing in the definition of alternatives that requires this relationship and, in fact, for focus alternatives, a number of studies have tested explicitly whether alternatives have to be co-hyponyms (Gotzner, 2015;Kim et al, 2015;Jördens et al, 2020): The answer is no. Still, it is interesting to ask why co-hyponymy is often used as a convenient shortcut in the operationalization of alternatives.…”
Section: Alternatives In the Labmentioning
confidence: 99%